Lex orandi, lex credendi? Il Messale Romano e il suo valore simbolico tra Summorum Pontificum e Traditionis Custodes (Stato, Chiese e pluralismo confessionale, 2021)
SOMMARIO: 1. Il “pomo della discordia”: Concilio Vaticano II - 2. L’ermeneutica della riforma nella continuità - 3. Unità nella unicità? - 4. Esempi di non trascurabile fedeltà.Lex orandi, lex credendi? The Roman Missal and its symbolic value between Summorum Pontificum and Traditionis CustodesABSTRACT: This essay aims to examine the symbolic value acquired by the Roman Missal of 1962 by the Second Vatican Council today, especially through the comparison of two recent statutes, Summorum Pontificum and Traditionis Custodes. They can represent an effective synthesis of the approaches used by the Catholic Church to relate to a liturgical question that is still very controversial.